Upaya Peningkatan Motivasi Belajar melalui Penerapan Pembelajaran Problem Based Learning Peserta Didik Kelas IX SMP Negeri 2 Pemulutan Selatan - Darmadi Darmadi (Departement of Mathematics Education, 2024)
This research aims to describe how efforts are made to increase learning motivation through the application of problem based learning for Class IX students at SMP Negeri 2 Pemulutan Selatan. This type of research is Classroom Action Research (PTK) which consists of 2 cycles. The subjects in this classroom action research (PTK) were students of Class IX of SMP Negeri 2 Pemulutan Selatan with the number of students being 20 people. The results of the research showed that in cycle I, the percentage of students' learning motivation questionnaire answers showed that only 13% of students had high learning motivation, while 25% of students had sufficient learning motivation, while there were 45% of students who lacked learning motivation. and 15% of students who have no motivation to learn. This means that, after implementing the problem based learning model, the learning motivation of class IX students at SMP Negeri 2 Pemulutan Selatan in cycle I experienced an increase in percentage of only 5%. Therefore, researchers continued research in cycle II. The percentage of students' learning motivation questionnaire answers showed that 70% of students had high learning motivation, while 25% of students had sufficient learning motivation, while there were 4% of students who lacked learning motivation and only 1% of students had have no motivation to learn. So it can be concluded that in the cycle there was a significant increase in learning motivation in class IX of SMP Negeri 2 Pemulutan Selatan showing that 95% of students were motivated to learn. This shows that the application of the problem based learning model with the improvements made after implementing cycle I has increased. In this case, the problem based learning model can increase students' learning motivation in learning mathematics on the subject of congruence of plane shapes and volume of cylinders in class IX SMP Negeri 2 Pemulutan Selatan.